Avaliação audiológica em pacientes com doenças reumáticas pediátricas - Flumian, Carolina Ferreira Campos [UNESP]; Magalhães, Claudia Saad [UNESP]; Montovani, Jair Cortez [UNESP] (FapUNIFESP (SciELO), 2013)
Purpose: To perform audiological assessment in children and adolescents followed up at a reference outpatient clinic for autoimmune diseases, regardless of specific diagnoses. Methods: A single-blind case-control study was conducted. Participants were 48 patients with ages from 5 to 19 years and one to 151 months follow-up, categorized into three groups: 15 control individuals with pain in limbs and no autoimmune disorders, 23 individuals with Juvenile Idiopathic Arthritis, and ten cases diagnosed with other autoimmune disorders. All subjects were submitted to clinical, otological, and audiological assessments (tympanometry, acoustic reflex, audiometry, speech audiometry, otoacoustic emissions, and auditory brainstem response test with click stimuli). Results: The group with other autoimmune disorders had a greater proportion of patients with symptoms and more altered results in the otoacoustic emission test, when compared with the control group and the group with Juvenile Idiopathic Arthritis. In the group with other autoimmune disorders, 50% of the subjects with no symptoms presented impaired acoustic reflexes, alterations in audiometry and in otoacoustic emissions. In the audiometry, the group with Juvenile Idiopathic Arthritis presented more alterations in higher frequencies, and the group with other autoimmune disorders, in lower frequencies. Conclusion: Symptoms related to hearing loss and audiological alterations were more frequent in children and adolescents with Juvenile Idiopathic Arthritis and other autoimmune disorders. The hearing alterations also occurred in patients with no symptoms, indicating the need for systematic hearing assessment for these patients in their clinical routine.

Realizar avaliação audiológica em crianças e adolescentes acompanhados em um ambulatório de referência para doenças autoimunes, independentemente do diagnóstico específico. MÉTODOS: Foi realizado um estudo cego simples do tipo caso-controle. Foram incluídos 48 pacientes com idades entre 5 e 19 anos e tempo de seguimento de um a 151 meses, divididos em três grupos: 15 pacientes controle com diagnóstico de dor em membros e exclusão de doença autoimune, 23 pacientes com Artrite Idiopática Juvenil, e dez pacientes com outras doenças autoimunes. Os voluntários foram submetidos a avaliações clínica, otológica e audiológica (timpanometria, pesquisa dos reflexos acústicos, audiometria, índice de reconhecimento de fala, emissões otoacústicas e potenciais evocados auditivos de tronco encefálico com estímulo click). RESULTADOS: O grupo com outras doenças autoimunes teve maior número de pacientes sintomáticos e maior número de orelhas alteradas no teste de emissões otoacústicas em comparação com o grupo controle e com o grupo com Artrite Idiopática Juvenil. Ainda no grupo com outras doenças autoimunes, 50% dos sujeitos assintomáticos apresentaram alterações na pesquisa dos reflexos, na audiometria e nas emissões otoacústicas. Na audiometria, o grupo com Artrite Idiopática Juvenil apresentou mais alterações nas frequências altas, e o grupo com outras doenças autoimunes, nas frequências baixas. CONCLUSÃO: Houve maior número de sintomas relacionados à perda auditiva e a alterações audiológicas em crianças e adolescentes com Artrite Idiopática Juvenil e outras doenças autoimunes. As alterações auditivas ocorreram também em pacientes assintomáticos, justificando-se a avaliação audiológica como rotina clínica desses pacientes.
Hearing loss assessment in patients with pediatric disorders
Keywords: Autoimmunity; Audiology; Hearing loss; Rheumatic diseases; Pediatrics; Autoimunidade; Audiologia; Deficiência auditiva; Doenças reumáticas; Pediatria